Mirta Rosenberg's Crumbs. Lesbian Traces in her Poetics of the Eighties (Anclajes, 2022)
The 1980s was a turning point for Argentine poetry. Marked by the public reappearance of words, ideas, and voices that had been silenced during the military dictatorship, there was also —as Alicia Genovese pointed out in La doble voz (1998)— the publication of numerous collections of poems written and signed by women authors. In this article I maintain that another remarkable phenomenon occurred within the same time frame and context, though for decades apparently unnoticed by poetry critics: more frequently and explicitly there appeared traces of lesbian sensibilities, bodies, affectivities and desires that began to modulate a heterogeneous yet multiple voice. I propose reading Mirta Rosenberg's work published in that decade —the poetry collections Pasajes (1984) and Madam (1988)— highlighting lesbian nuances which run sublty through the verses and structure one of the most influential and irreverent voices of Argentine poetry in recent years.
Keywords: Argentine poetry; Mirta Rosenberg; LGBT and Queer Literary Studies; Lesbian affectivity